Aqueous flame retardant coating for wood and preparation method thereof
By applying an aqueous flame retardant coating liquid on wood, using components such as epoxy resin, phosphorus-containing polyvinyl alcohol and crosslinking agent, the problem of flammability of wood is solved, and the flame retardant performance and deformation resistance are achieved. and water resistance.
Patent Information
- Application Number
- CN202411133722.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-19
AI Technical Summary
Due to its flammability, wood has safety risks, and the prior art has failed to effectively solve this problem.
A water-based flame retardant coating liquid for wood is used to react with epoxy resin and phosphorus-containing polyvinyl alcohol and flame retardant crosslinking agent in an organic solvent, functional filler is added, and the aqueous flame retardant coating liquid is formed by adding water. Coated at high temperature after coating on the surface of the wood.
It significantly improves the flame retardant properties, deformation resistance and water resistance of wood, ensuring the safety and stability of wood during combustion.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wood flame retardancy, in particular to a water-based flame retardant coating liquid for wood and a preparation method thereof. Background Art
[0002] Wood has the advantages of good mechanical properties, low cost, green and environmentally friendly, non-toxic, processable, renewable, etc., and is widely used as a building, decoration, and structural material. At the same time, wood itself has strong water absorption and is greatly affected by the external environment. Its loose structure, easy corrosion, flammability, shrinkage and swelling, and easy deformation make wood limited in practical applications. With the advancement of science and technology, people use impregnation coating, surface modification, sol-gel method, etc. to treat wood to achieve the desired effect. For example, Chinese patent CN201910671862.X self-emulsifying antibacterial water-based epoxy resin and its application in wood and bamboo protection discloses a water-based epoxy resin, in which epoxy resin is reacted with diethanolamine and polyetheramine in an organic solvent in turn to form an epoxy resin cross-linked product with hydrophilic hydroxyl groups, the wood is bonded, and then quaternized with glacial acetic acid to provide antibacterial properties, thereby improving the defects of wood being easy to deform and decay. However, the patent does not deal with the flammability disadvantages of wood, which poses a safety hazard. Therefore, we propose an aqueous flame retardant coating for wood and a preparation method thereof. Summary of the invention
[0003] The object of the present invention is to provide an aqueous flame retardant coating for wood and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a water-based flame retardant coating for wood, comprising the following components: by mass, 100 parts of epoxy resin, 24 to 32 parts of phosphorus-containing polyvinyl alcohol, 30 to 50 parts of cross-linking agent, 100 parts of organic solvent, 8 to 12 parts of functional filler, 3 to 8 parts of additives and water.
[0005] Furthermore, the functionalized filler is obtained by modifying the filler with epoxysiloxane;
[0006] The filler is a mixture of one or more of ammonium polyphosphate, aluminum hypophosphite, aluminum hydroxide, magnesium hydroxide, zinc borate, basalt, calcium carbonate, mica powder, talc, silicon dioxide, titanium dioxide, graphene, clay, montmorillonite, and graphite fiber.
[0007] Furthermore, the auxiliary agent includes 1 to 3 parts of a thickener and 2 to 5 parts of a mildew preventer.
[0008] Furthermore, the solid content of the aqueous flame retardant coating is 20% to 30%.
[0009] Furthermore, the phosphorus-containing polyvinyl alcohol is obtained by oxidizing polyvinyl alcohol and reacting with DOPO.
[0010] A method for preparing a water-based flame-retardant coating for wood, comprising the following processes:
[0011] Mix epoxy resin and phosphorus-containing polyvinyl alcohol in an organic solvent, heat to 70-80°C under nitrogen atmosphere, add catalyst, heat to 110-120°C, and react for 120-180 minutes;
[0012] Add a cross-linking agent and a functional filler, and keep the mixture warm at 70 to 80° C. for 60 to 90 minutes; add deionized water, perform shearing, and add an auxiliary agent to obtain a water-based flame retardant coating.
[0013] Further, the water-based flame retardant coating liquid comprises the following components: by mass, 100 parts of epoxy resin, 24 to 32 parts of phosphorus-containing polyvinyl alcohol, 30 to 50 parts of a cross-linking agent, 100 parts of an organic solvent, and 8 to 12 parts of a functional filler;
[0014] The catalyst is aluminum chloride·propylene glycol complex, and the dosage is 0.9% to 1.2% of the total mass of epoxy resin and phosphorus-containing polyvinyl alcohol.
[0015] Furthermore, the organic solvent is N,N-dimethylformamide; before shearing, deionized water is added and removed by rotary evaporation at 80°C.
[0016] Furthermore, the shearing process conditions are: at a rotation speed of 8000-13000 rpm, at a temperature of 65-70° C., and emulsification for 100-150 seconds.
[0017] Furthermore, the phosphorus-containing polyvinyl alcohol is prepared by the following process:
[0018] Mix polyvinyl alcohol and deionized water, heat to 90-95°C to dissolve; add potassium permanganate, stir and react for 5-10 minutes; filter, take the filtrate and distill under reduced pressure, and vacuum dry to obtain oxidized polyvinyl alcohol;
[0019] The oxidized polyvinyl alcohol and DOPO are mixed, and stirred at 70-80° C. for 30-60 minutes; toluene is added, and the temperature is raised to 110-115° C., and the reaction is refluxed for 100-150 minutes; the mixture is cooled, filtered, and vacuum dried to obtain phosphorus-containing polyvinyl alcohol.
[0020] In the above technical scheme, epoxy resin is mixed with phosphorus-containing polyvinyl alcohol, and the temperature is raised. Under the action of a catalyst, epoxy reacts with hydroxyl to form an epoxy resin-phosphorus-containing polyvinyl alcohol copolymer, and its molecular structure contains hydrophilic groups such as phosphoric acid, hydroxyl and hydrophobic epoxy groups, which make it amphiphilic, so that it can be prepared with water-based epoxy resin after water shearing, and can improve the plasticity of the coating liquid after curing (recorded as a cured layer). The crosslinking agent is crosslinked and mixed with the epoxy resin, and fillers and additives are added to prepare a coating liquid (aqueous flame retardant coating liquid), which is applied to cover and penetrate the wood surface; then it is cured at high temperature, and the coating liquid is fixed and adhered to the wood surface and inside, and a crosslinked network is formed to improve the water resistance, deformation resistance and flame retardancy of the cured wood (wood treated with the water-based flame retardant coating liquid).
[0021] Further, the mass ratio of polyvinyl alcohol to potassium permanganate is 10:(4.5-5.0);
[0022] The ratio of polyvinyl alcohol to deionized water is 10g: (90-100) mL.
[0023] Further, the mass ratio of oxidized polyvinyl alcohol to DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is 10:(6.3-6.9);
[0024] The ratio of oxidized polyvinyl alcohol to toluene is 10 g: (20-30) mL.
[0025] In the above technical scheme, the hydroxyl groups in polyvinyl alcohol are oxidized to carbonyl groups by potassium permanganate, and then react with the phosphoric acid groups in DOPO to form phosphorus-containing polyvinyl alcohol. Without consuming the hydroxyl groups in polyvinyl alcohol, the phosphate ester is introduced into the coating liquid (water-based flame retardant coating liquid) system, which can effectively improve the thermal stability of the cured layer. During combustion, the system can play a synergistic flame retardant role of the gas phase and the condensed phase. The system absorbs heat and releases phosphoric acid and polyphosphoric acid to dilute the combustible gas, and catalyzes the dehydration and carbonization of organic matter, thereby isolating the air from the combustibles and improving its flame retardant properties. The steric hindrance between the polymer molecular chains is increased, which helps to improve the deformation resistance, chemical resistance, weather resistance and other capabilities of the cured wood.
[0026] Furthermore, the functionalized filler is prepared by the following process:
[0027] The filler, 3-glycidyloxypropyltrimethoxysilane and alcohol aqueous solution are mixed, the temperature is raised to 60-80° C., and the mixture is stirred for reaction for 3-5 hours; the mixture is filtered, washed, and dried to obtain the product.
[0028] Further, the mass ratio of filler and 3-glycidyloxypropyltrimethoxysilane is 10:(0.3-1.0);
[0029] The ratio of filler to alcohol aqueous solution is (1.0-1.5) g / 100 mL.
[0030] In the above technical scheme, the filler is surface-modified by siloxane, and the filler is functionalized so that its surface is loaded with epoxy groups and can participate in the coating liquid reaction. The filler is grafted into the epoxy resin cross-linking system, which can effectively improve the dispersibility of the filler in the coating liquid, increase the cross-linking degree of the system, improve its mechanical properties, and improve its flame retardancy and water resistance.
[0031] Further, the cross-linking agent is prepared by the following process:
[0032] Step 1, 1,1-dimethoxysilylcyclobutane, octamethylcyclotetrasiloxane, a catalyst and deionized water are mixed, and the temperature is raised to 80-85° C. under the protection of a nitrogen atmosphere, and the reaction is carried out for 100-150 minutes; the temperature is raised to 90-95° C., dimethylethoxysilylethylamine is added, and the reaction is continued for 4-5 hours; the temperature is raised to 150° C., the catalyst is decomposed at high temperature, and low molecular weight compounds are removed by reduced pressure distillation to obtain amino-terminated siloxane;
[0033] The amino-terminated siloxane was heated to 70-75°C, dimethylallylsilylethanol was slowly added, and the mixture was stirred for 24 hours to obtain silanolamine;
[0034] Step 2, DOPO is mixed with toluene, heated to 85-90°C, and stirred for 20-30 minutes; 4-hydroxy-N-(4-hydroxyphenyl)benzamide is added, the temperature is raised to 110-120°C, and refluxed for 7-8 hours; cooled, filtered, and vacuum dried to obtain DOPO-based bisphenol;
[0035] Step 3, mixing silanolamine and boric acid in toluene, heating to 110-120° C., and reflux reaction for 8-10 hours; removing water and toluene produced by esterification by azeotropic removal, and vacuum drying to obtain boric acid alcoholamine ester;
[0036] Mix boric acid alcohol amine ester and solvent, add polyformaldehyde and DOPO-based bisphenol, raise the temperature to 80-100°C, and react at a constant temperature for 8-10 hours; remove the solvent by vacuum distillation, and dissolve with dichloromethane; wash with 5% sodium bicarbonate solution, wash with water, and vacuum dry at 60°C for 2-8 hours to obtain a cross-linking agent.
[0037] Furthermore, in step 1, the amino-terminated siloxane comprises the following components: by mole, 1 to 8 parts of 1,1-dimethoxysilylcyclobutane, 2 to 9 parts of octamethylcyclotetrasiloxane, 4 to 25 parts of deionized water, and 2 to 6 parts of dimethylethoxysilylethylamine;
[0038] In terms of molar amount, the amount of deionized water used is ≥ the amount of 1,1-dimethoxysilylcyclobutane used × 2 + the amount of dimethylethoxysilylethylamine used;
[0039] The catalyst is tetramethylammonium hydroxide, and the amount used is 0.5% to 1.0% of the total mass of the reaction system.
[0040] Furthermore, in step 1, the mass ratio of amino-terminated siloxane to dimethylallylsilylethanol is 100:(5.9-21.5).
[0041] Furthermore, in step 2, the molar ratio of DOPO and 4-hydroxy-N-(4-hydroxyphenyl)benzamide (CAS: 22744-42-9) is 1:1;
[0042] The ratio of DOPO to toluene was 10 g / 100 mL.
[0043] Furthermore, in step 3, the mass ratio of silanolamine to boric acid is (45-158):1;
[0044] The ratio of silanolamine to toluene is (12-20) g / 100 mL.
[0045] Furthermore, in step 3, the mass ratio of paraformaldehyde, boric acid alcohol amine ester, and DOPO-based bisphenol is 1: (25.3-81.4): (3.5-3.9);
[0046] The solvent is a toluene / ethanol solution, and the volume ratio of toluene to ethanol is 1:1;
[0047] The ratio of boric acid alcohol amine ester to solvent is 10 g / 100 mL.
[0048] In the above technical scheme, under the action of the catalyst tetramethylammonium hydroxide, 1,1-dimethoxysilylcyclobutane and octamethylcyclotetrasiloxane are polymerized through silicon-oxygen bonds and terminated with dimethylethoxysilylethylamine to form a polycarbosilane having an amino-terminated and silicon-based cyclobutane structure. Introducing it into the molecular structure of the coating liquid can effectively improve its thermal stability and water resistance, and participate in the formation of a carbon layer of the cured layer during combustion, making it more compact, further improving the barrier of the carbon layer to the external combustion environment, thereby improving the flame retardant properties of the cured layer; it is recorded as amino-terminated siloxane.
[0049] The amino-terminated siloxane is added to dimethylallylsilylethanol, and one end of the siloxane is hydroxyl by controlling the reaction process. The reaction product is recorded as silanolamine. The silanolamine is mixed with boric acid, and the polyhydroxyl group reacts with the boric acid to form a trifunctional boric acid alcoholamine ester. The increase in functionality helps to improve the crosslinking degree of the epoxy crosslinking system, promote the improvement of the mechanical properties of the cured layer and the water resistance and deformation resistance of the cured wood. It can also introduce elemental boron into the cured layer, which can serve as a component of the carbon layer during combustion and participate in the establishment of the glass cover layer, further improve the insulation ability of the carbon layer, and play a condensed phase flame retardant role.
[0050] DOPO is added to 4-hydroxy-N-(4-hydroxyphenyl)benzamide to form a bisphenol compound with a DOPO group, which is recorded as DOPO-based bisphenol. Boric acid alcohol amine ester reacts with polyformaldehyde and DOPO-based bisphenol to form a benzoxazine structure. By controlling the reaction process, a benzoxazine polymer containing an amino group at the end group is obtained, which can react with epoxy resin and is recorded as a cross-linking agent. The introduction of structures such as benzoxazine and DOPO further improves the deformation resistance, thermal stability and flame retardancy of the cured layer. The cross-linking and curing of the cross-linking agent with flame retardant ability with epoxy resin can effectively improve the anti-loss ability of the flame retardant, and the flame retardant ability of the wood can be maintained for a long time.
[0051] The invention discloses an application of a water-based flame retardant coating liquid for wood. The water-based flame retardant coating liquid is taken, and wood is coated or impregnated with the coating liquid, and then cured to form a cured layer, thereby obtaining cured wood.
[0052] Furthermore, the curing process is: curing at 60-80°C for 60 minutes, curing at 100-110°C for 60 minutes, and curing at 120-130°C for 60 minutes.
[0053] Furthermore, the coating thickness of the water-based flame retardant coating on the wood surface is 0.3 to 0.7 mm.
[0054] Furthermore, the impregnation adopts high-pressure impregnation with a pressure of 0.5 to 1.0 MPa and a duration of 90 to 150 minutes.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] 1. The present invention discloses a water-based flame-retardant coating for wood and a preparation method thereof. The water-based flame-retardant coating is formed by reacting epoxy resin with phosphorus-containing polyvinyl alcohol and a flame-retardant crosslinking agent in an organic solvent, adding a functional filler, and adding water and shearing, so that the treated wood has better deformation resistance and flame retardancy.
[0057] 2. The present invention discloses an aqueous flame-retardant coating for wood and a preparation method thereof. The hydroxyl group in polyvinyl alcohol is oxidized into a carbonyl group by the oxidation action of potassium permanganate, and reacts with DOPO to form phosphorus-containing polyvinyl alcohol. Phosphoric acid is introduced into the coating system, which can effectively improve the thermal stability of the cured layer and exert its gas phase and condensed phase synergistic flame retardant effect, thereby improving the water resistance, deformation resistance and flame retardancy of the cured wood.
[0058] 3. The water-based flame-retardant coating for wood of the present invention and its preparation method, the surface of the filler is modified by siloxane so that the surface of the filler is loaded with epoxy groups so that it can participate in the reaction, and the filler is grafted into the epoxy resin cross-linking system, which effectively improves the dispersibility of the filler in the coating and improves the mechanical properties and flame retardancy of the cured layer.
[0059] 4. The present invention provides an aqueous flame retardant coating for wood and a preparation method thereof. A crosslinking agent is prepared from components such as 1,1-dimethoxysilylcyclobutane, octamethylcyclotetrasiloxane, dimethylallylsilylethanol, boric acid DOPO, 4-hydroxy-N-(4-hydroxyphenyl)benzamide, etc., so that the coating has flame retardancy and crosslinkability. The coating can be crosslinked and cured with epoxy resin to effectively improve the flame retardancy, water resistance and deformation resistance of wood. DETAILED DESCRIPTION
[0060] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] In the following specific implementations,
[0062] Epoxy resin: E44, from Bluestar Chemical New Materials Co., Ltd.;
[0063] Polyvinyl alcohol: average Mw 13000, 98% hydrolyzed, from Aladdin Reagent (Shanghai) Co., Ltd.
[0064] The filler is ammonium polyphosphate and basalt, with a mass ratio of 7:3;
[0065] Basalt: 6000 mesh, from Tianjin Silicate Research Institute;
[0066] Ammonium polyphosphate: A189185, n≥1000, from Aladdin Reagent (Shanghai) Co., Ltd.;
[0067] Thickener: C-340, from Guangdong Zhongke Hongtai New Materials Co., Ltd.;
[0068] Antifungal agent: iHeir-MA wood antifungal agent, from Guangzhou Aihaoer Antifungal and Antibacterial Technology Co., Ltd.;
[0069] Polyetheramine: D400, from Shijiazhuang Hejia Chemical Co., Ltd.;
[0070] The following implementation methods are all laboratory tests and can be expanded proportionally according to needs;
[0071] The experimental wood is poplar, which comes from Changsha, Hunan, and is dried to 4% to 8% before use.
[0072] Embodiment 1: A method for preparing a water-based flame retardant coating for wood, comprising the following process:
[0073] Step 1, preparation of phosphorus-containing polyvinyl alcohol:
[0074] Mix 10g polyvinyl alcohol and 90mL deionized water, heat to 90°C to dissolve; add 4.5g potassium permanganate, stir and react for 5min; filter, take the filtrate and distill under reduced pressure, and vacuum dry to obtain oxidized polyvinyl alcohol;
[0075] 10 g of oxidized polyvinyl alcohol and 6.3 g of DOPO were mixed and stirred at 70°C for 30 min; 20 mL of toluene was added, the temperature was raised to 110°C, and the reaction was refluxed for 100 min; the mixture was cooled, filtered, and vacuum dried to obtain phosphorus-containing polyvinyl alcohol;
[0076] Step 2: Preparation of functionalized filler:
[0077] Mix 10 g of filler, 0.3 g of 3-glycidyloxypropyltrimethoxysilane and 67 mL of alcohol aqueous solution, heat to 60° C., and stir to react for 3 h; filter, wash, and dry to obtain a functionalized filler;
[0078] Step 3, preparation of cross-linking agent:
[0079] (1) 1,1-dimethoxysilylcyclobutane, octamethylcyclotetrasiloxane, 0.5% catalyst tetramethylammonium hydroxide and deionized water are mixed, and the temperature is raised to 80°C for reaction for 100 minutes under nitrogen atmosphere protection; the temperature is raised to 90°C, dimethylethoxysilylethylamine is added, and the reaction is continued for 4 hours; the temperature is raised to 150°C, the catalyst is decomposed at high temperature, and low molecular weight compounds are removed by reduced pressure distillation to obtain amino-terminated siloxane; the amino-terminated siloxane includes the following components: in terms of molar amount, 1 part of 1,1-dimethoxysilylcyclobutane, 9 parts of octamethylcyclotetrasiloxane, 4 parts of deionized water, and 2 parts of dimethylethoxysilylethylamine;
[0080] Heat 100 g of amino-terminated siloxane to 70°C, slowly add 21.5 g of dimethylallylsilylethanol, and stir to react for 24 h to obtain silanolamine;
[0081] (2) Mix 10 g of DOPO in 100 mL of toluene, heat to 85 °C, and stir for 20 min; add 9.9 g of 4-hydroxy-N-(4-hydroxyphenyl)benzamide, heat to 110 °C, and reflux for 7 h; cool, filter, and vacuum dry to obtain DOPO-based bisphenol;
[0082] (3) Mixing silanolamine and boric acid in toluene, heating to 110°C, and reflux for 8 hours; removing water and toluene produced by esterification by azeotropic removal, and vacuum drying to obtain boric acid amine ester; the mass ratio of silanolamine to boric acid is 158:1; the ratio of silanolamine to toluene is 20g / 100mL;
[0083] Mix boric acid alcohol amine ester and solvent (toluene / ethanol solution with a volume ratio of 1:1), add paraformaldehyde and DOPO-based bisphenol, heat to 80°C, and react at constant temperature for 8 hours; remove the solvent by vacuum distillation, dissolve with dichloromethane; wash with 5% sodium bicarbonate solution, wash with water, and vacuum dry at 60°C for 8 hours to obtain a cross-linking agent; the mass ratio of paraformaldehyde, boric acid alcohol amine ester, and DOPO-based bisphenol is 1:81.4:3.5; the ratio of boric acid alcohol amine ester to solvent is 10g / 100mL;
[0084] Step 4: Preparation of water-based flame retardant coating:
[0085] Mix epoxy resin and phosphorus-containing polyvinyl alcohol in an organic solvent, N,N-dimethylformamide, and heat to 70°C under nitrogen atmosphere. Add a catalyst and heat to 110°C for 120 minutes. Add a crosslinking agent and a functional filler and keep the temperature at 70°C for 60 minutes.
[0086] Deionized water (10 times the volume of N,N-dimethylformamide) was added, and the N,N-dimethylformamide was removed by rotary evaporation at 80°C. Deionized water was added again, and the mixture was emulsified at a speed of 8000 rpm and a temperature of 65°C for 150 seconds. Adding additives, an aqueous flame retardant coating having a solid content of 25% was obtained. The aqueous flame retardant coating comprises the following components: by mass, 100 parts of epoxy resin, 24 parts of phosphorus-containing polyvinyl alcohol, 30 parts of a cross-linking agent, 100 parts of an organic solvent, 8 parts of a functional filler, and 3 parts of additives, wherein the additives include 1 part of a thickener and 2 parts of a mildewproofing agent.
[0087] Embodiment 2: A method for preparing a water-based flame retardant coating for wood, comprising the following process:
[0088] Step 1, preparation of phosphorus-containing polyvinyl alcohol:
[0089] Mix 10g polyvinyl alcohol and 95mL deionized water, heat to 92°C to dissolve; add 4.8g potassium permanganate, stir and react for 8min; filter, take the filtrate and distill under reduced pressure, and vacuum dry to obtain oxidized polyvinyl alcohol;
[0090] 10 g of oxidized polyvinyl alcohol and 6.6 g of DOPO were mixed and stirred at 75°C for 45 min; 25 mL of toluene was added, the temperature was raised to 112°C, and the reaction was refluxed for 120 min; the mixture was cooled, filtered, and vacuum dried to obtain phosphorus-containing polyvinyl alcohol;
[0091] Step 2: Preparation of functionalized filler:
[0092] Mix 10 g of filler, 0.6 g of 3-glycidyloxypropyltrimethoxysilane and 80 mL of alcohol aqueous solution, heat to 70° C., and stir to react for 4 hours; filter, wash, and dry to obtain a functionalized filler;
[0093] Step 3, preparation of cross-linking agent:
[0094] (1) 1,1-dimethoxysilylcyclobutane, octamethylcyclotetrasiloxane, 0.8% catalyst tetramethylammonium hydroxide and deionized water are mixed, and the temperature is raised to 82°C for reaction for 120 minutes under the protection of nitrogen atmosphere; the temperature is raised to 92°C, dimethylethoxysilylethylamine is added, and the reaction is continued for 4.5 hours; the temperature is raised to 150°C, the catalyst is decomposed at high temperature, and low molecular weight compounds are removed by reduced pressure distillation to obtain amino-terminated siloxane; the amino-terminated siloxane includes the following components: 4 parts of 1,1-dimethoxysilylcyclobutane, 6 parts of octamethylcyclotetrasiloxane, 12 parts of deionized water, and 4 parts of dimethylethoxysilylethylamine in molar amount;
[0095] Heat 100 g of amino-terminated siloxane to 72°C, slowly add 10.0 g of dimethylallylsilylethanol, and stir to react for 24 h to obtain silanolamine;
[0096] (2) Mix 10 g of DOPO in 100 mL of toluene, heat to 88 °C, and stir for 25 min; add 9.9 g of 4-hydroxy-N-(4-hydroxyphenyl)benzamide, heat to 115 °C, and reflux for 7.5 h; cool, filter, and vacuum dry to obtain DOPO-based bisphenol;
[0097] (3) Mixing silanolamine and boric acid in toluene, heating to 115°C, and reflux for 9 hours; removing water and toluene produced by esterification by azeotropic removal, and vacuum drying to obtain boric acid amine ester; the mass ratio of silanolamine to boric acid is 78:1; the ratio of silanolamine to toluene is 18 g / 100 mL;
[0098] Mix boric acid alcohol amine ester and solvent (toluene / ethanol solution with a volume ratio of 1:1), add polyformaldehyde and DOPO-based bisphenol, heat to 90°C, and react at constant temperature for 9 hours; remove the solvent by vacuum distillation, dissolve with dichloromethane; wash with 5% sodium bicarbonate solution, wash with water, and vacuum dry at 60°C for 8 hours to obtain a cross-linking agent; the mass ratio of polyformaldehyde, boric acid alcohol amine ester, and DOPO-based bisphenol is 1:40:3.7; the ratio of boric acid alcohol amine ester to solvent is 10g / 100mL;
[0099] Step 4: Preparation of water-based flame retardant coating:
[0100] Mix epoxy resin and phosphorus-containing polyvinyl alcohol in an organic solvent, N,N-dimethylformamide, and heat to 75°C under a nitrogen atmosphere. Add a catalyst and heat to 115°C for 150 minutes. Add a crosslinking agent and a functional filler and keep the temperature at 75°C for 75 minutes.
[0101] Deionized water (10 times the volume of N,N-dimethylformamide) was added, and the N,N-dimethylformamide was removed by rotary evaporation at 80°C. Deionized water was added again, and the mixture was emulsified at a speed of 10,000 rpm and a temperature of 68°C for 120 seconds. Adding additives, an aqueous flame retardant coating having a solid content of 25% was obtained. The aqueous flame retardant coating comprises the following components: by mass, 100 parts of epoxy resin, 28 parts of phosphorus-containing polyvinyl alcohol, 40 parts of a cross-linking agent, 100 parts of an organic solvent, 10 parts of a functional filler, and 5 parts of additives, wherein the additives include 2 parts of a thickener and 3 parts of a mildewproofing agent.
[0102] Embodiment 3: A method for preparing a water-based flame retardant coating for wood, comprising the following process:
[0103] Step 1, preparation of phosphorus-containing polyvinyl alcohol:
[0104] Mix 10g of polyvinyl alcohol and 100mL of deionized water, heat to 95°C to dissolve; add 5.0g of potassium permanganate, stir and react for 10min; filter, take the filtrate and distill under reduced pressure, and vacuum dry to obtain oxidized polyvinyl alcohol;
[0105] 10 g of oxidized polyvinyl alcohol and 6.9 g of DOPO were mixed and stirred at 80°C for 60 min; 30 mL of toluene was added, the temperature was raised to 115°C, and the reaction was refluxed for 150 min; the mixture was cooled, filtered, and vacuum dried to obtain phosphorus-containing polyvinyl alcohol;
[0106] Step 2: Preparation of functionalized filler:
[0107] Mix 10 g of filler, 1.0 g of 3-glycidyloxypropyltrimethoxysilane and 100 mL of alcohol aqueous solution, heat to 80° C., and stir to react for 5 hours; filter, wash, and dry to obtain a functionalized filler;
[0108] Step 3, preparation of cross-linking agent:
[0109] (1) 1,1-dimethoxysilylcyclobutane, octamethylcyclotetrasiloxane, 1.0% tetramethylammonium hydroxide catalyst and deionized water are mixed, and the temperature is raised to 85°C for reaction for 150 minutes under nitrogen atmosphere protection; the temperature is raised to 95°C, dimethylethoxysilylethylamine is added, and the reaction is continued for 5 hours; the temperature is raised to 150°C, the catalyst is decomposed at high temperature, and low molecular weight compounds are removed by reduced pressure distillation to obtain amino-terminated siloxane; the amino-terminated siloxane includes the following components: 8 parts of 1,1-dimethoxysilylcyclobutane, 2 parts of octamethylcyclotetrasiloxane, 25 parts of deionized water, and 6 parts of dimethylethoxysilylethylamine in molar amount;
[0110] Heat 100 g of amino-terminated siloxane to 75°C, slowly add 5.9 g of dimethylallylsilylethanol, and stir to react for 24 h to obtain silanolamine;
[0111] (2) Mix 10 g of DOPO in 100 mL of toluene, heat to 90 °C, and stir for 30 min; add 9.9 g of 4-hydroxy-N-(4-hydroxyphenyl)benzamide, heat to 120 °C, and reflux for 8 h; cool, filter, and vacuum dry to obtain DOPO-based bisphenol;
[0112] (3) Mixing silanolamine and boric acid in toluene, heating to 120°C, and reflux for 10 hours; removing water and toluene produced by esterification by azeotropic removal, and vacuum drying to obtain boric acid amine ester; the mass ratio of silanolamine to boric acid is 48:1; the ratio of silanolamine to toluene is 12 g / 100 mL;
[0113] Mix boric acid alcohol amine ester and solvent (toluene / ethanol solution with a volume ratio of 1:1), add polyformaldehyde and DOPO-based bisphenol, heat to 100°C, and react at constant temperature for 10 hours; remove the solvent by vacuum distillation, dissolve with dichloromethane; wash with 5% sodium bicarbonate solution, wash with water, and vacuum dry at 60°C for 8 hours to obtain a cross-linking agent; the mass ratio of polyformaldehyde, boric acid alcohol amine ester, and DOPO-based bisphenol is 1:25.3:3.9; the ratio of boric acid alcohol amine ester to solvent is 10g / 100mL;
[0114] Step 4: Preparation of water-based flame retardant coating:
[0115] Mix epoxy resin and phosphorus-containing polyvinyl alcohol in an organic solvent, N,N-dimethylformamide, and heat to 80°C under nitrogen atmosphere protection. Add a catalyst, heat to 120°C, and react for 180 minutes. Add a crosslinking agent and a functional filler, and keep the temperature at 80°C for 90 minutes.
[0116] Deionized water (10 times the volume of N,N-dimethylformamide) was added, and the N,N-dimethylformamide was removed by rotary evaporation at 80°C. Deionized water was added again, and the mixture was emulsified at a speed of 13000 rpm and a temperature of 70°C for 100 seconds. Adding additives, an aqueous flame retardant coating having a solid content of 25% was obtained. The aqueous flame retardant coating comprises the following components: by mass, 100 parts of epoxy resin, 32 parts of phosphorus-containing polyvinyl alcohol, 50 parts of a cross-linking agent, 100 parts of an organic solvent, 12 parts of a functional filler, and 8 parts of additives, wherein the additives include 3 parts of a thickener and 5 parts of a mildewproofing agent.
[0117] Comparative Example 1: A method for preparing a water-based flame retardant coating for wood, comprising the following process:
[0118] Step 3, preparation of cross-linking agent:
[0119] 1,1-dimethoxysilylcyclobutane, octamethylcyclotetrasiloxane, 0.5% catalyst tetramethylammonium hydroxide and deionized water are mixed, and the temperature is raised to 80°C for reaction for 100 minutes under the protection of nitrogen atmosphere; the temperature is raised to 90°C, dimethylethoxysilylethylamine is added, and the reaction is continued for 4 hours; the temperature is raised to 150°C, the catalyst is decomposed at high temperature, and low molecular weight compounds are removed by reduced pressure distillation to obtain amino-terminated siloxane; the amino-terminated siloxane includes the following components: in terms of molar amount, 1 part of 1,1-dimethoxysilylcyclobutane, 9 parts of octamethylcyclotetrasiloxane, 4 parts of deionized water, and 2 parts of dimethylethoxysilylethylamine;
[0120] Heat 100 g of amino-terminated siloxane to 70°C, slowly add 21.5 g of dimethylallylsilylethanol, and stir to react for 24 h to obtain silanolamine;
[0121] The silanolamine and boric acid are mixed in toluene, heated to 110°C, and refluxed for 8 hours; water and toluene produced by esterification are removed by azeotropy, and vacuum dried to obtain a crosslinking agent; the mass ratio of silanolamine to boric acid is 158:1; the ratio of silanolamine to toluene is 20g / 100mL;
[0122] The water-based flame retardant coating liquid includes the following components: by mass, 100 parts of epoxy resin, 24 parts of phosphorus-containing polyvinyl alcohol, 30 parts of cross-linking agent, 100 parts of organic solvent, 8 parts of functional filler, 3 parts of auxiliary agent, the auxiliary agent includes 1 part of thickener, 2 parts of mildewproof agent;
[0123] The other processes of step 1-2 and step 4 are the same as those in Example 1 to obtain a water-based flame retardant coating liquid.
[0124] Comparative Example 2: A method for preparing a water-based flame retardant coating for wood, comprising the following process:
[0125] Step 3, preparation of cross-linking agent:
[0126] Mix ethanolamine and boric acid in toluene, heat to 110°C, and reflux for 8 hours; remove water and toluene produced by esterification by azeotropic removal, and vacuum dry to obtain boric acid ethanolamine ester; the mass ratio of ethanolamine 45 to boric acid 61.8 is 2.2:1; the ratio of ethanolamine to toluene is 20g / 100mL;
[0127] Mix boric acid alcohol amine ester and solvent (toluene / ethanol solution with a volume ratio of 1:1), add paraformaldehyde and DOPO-based bisphenol, heat to 80°C, and react at constant temperature for 8 hours; remove the solvent by vacuum distillation, dissolve with dichloromethane; wash with 5% sodium bicarbonate solution, wash with water, and vacuum dry at 60°C for 8 hours to obtain a cross-linking agent; the mass ratio of paraformaldehyde, boric acid alcohol amine ester, and DOPO-based bisphenol is 1:1.6:3.5; the ratio of boric acid alcohol amine ester to solvent is 10g / 100mL;
[0128] The water-based flame retardant coating liquid includes the following components: by mass, 100 parts of epoxy resin, 24 parts of phosphorus-containing polyvinyl alcohol, 30 parts of cross-linking agent, 100 parts of organic solvent, 8 parts of functional filler, 3 parts of auxiliary agent, the auxiliary agent includes 1 part of thickener, 2 parts of mildewproof agent;
[0129] The other processes of step 1-2 and step 4 are the same as those in Example 1 to obtain a water-based flame retardant coating liquid.
[0130] Comparative Example 3: A method for preparing a water-based flame retardant coating for wood, comprising the following process:
[0131] Step 3, preparation of cross-linking agent:
[0132] Mix ethanolamine and boric acid in toluene, heat to 110°C, and reflux for 8 hours; remove water and toluene produced by esterification by azeotropic removal, and vacuum dry to obtain boric acid ethanolamine ester; the mass ratio of ethanolamine 45 to boric acid 61.8 is 2.2:1; the ratio of ethanolamine to toluene is 20g / 100mL;
[0133] Mix boric acid alcohol amine ester and solvent (toluene / ethanol solution with a volume ratio of 1:1), add paraformaldehyde and bisphenol A, heat to 80°C, and react at constant temperature for 8 hours; remove the solvent by vacuum distillation, dissolve with dichloromethane; wash with 5% sodium bicarbonate solution, wash with water, and vacuum dry at 60°C for 8 hours to obtain a cross-linking agent; the mass ratio of paraformaldehyde, boric acid alcohol amine ester and bisphenol A is 1:1.6:1.9; the ratio of boric acid alcohol amine ester and solvent is 10g / 100mL;
[0134] The water-based flame retardant coating liquid includes the following components: by mass, 100 parts of epoxy resin, 24 parts of phosphorus-containing polyvinyl alcohol, 30 parts of cross-linking agent, 100 parts of organic solvent, 8 parts of functional filler, 3 parts of auxiliary agent, the auxiliary agent includes 1 part of thickener, 2 parts of mildewproof agent;
[0135] The other processes of step 1-2 and step 4 are the same as those in Example 1 to obtain a water-based flame retardant coating liquid.
[0136] Comparative Example 4: A method for preparing a water-based flame retardant coating for wood, comprising the following process:
[0137] Step 3: Use polyetheramine as a cross-linking agent:
[0138] The water-based flame retardant coating liquid includes the following components: by mass, 100 parts of epoxy resin, 24 parts of phosphorus-containing polyvinyl alcohol, 30 parts of cross-linking agent, 100 parts of organic solvent, 8 parts of functional filler, 3 parts of auxiliary agent, the auxiliary agent includes 1 part of thickener, 2 parts of mildewproof agent;
[0139] The other processes of step 1-2 and step 4 are the same as those in Example 1 to obtain a water-based flame retardant coating liquid.
[0140] Comparative Example 5: A method for preparing a water-based flame retardant coating for wood, comprising the following process:
[0141] Step 1: Preparation of functionalized filler:
[0142] Mix 10 g of filler, 0.3 g of 3-glycidyloxypropyltrimethoxysilane and 67 mL of alcohol aqueous solution, heat to 60° C., and stir to react for 3 h; filter, wash, and dry to obtain a functionalized filler;
[0143] Step 2: Preparation of water-based flame retardant coating:
[0144] Epoxy resin and diethanolamine were mixed in an organic solvent, propylene glycol monomethyl ether, and the temperature was raised to 70°C under nitrogen atmosphere for 120 minutes. A crosslinking agent and a functional filler were added, and the mixture was kept at 70°C for 60 minutes.
[0145] Rotary evaporation was performed to remove N,N-dimethylformamide. Deionized water was added, and the mixture was emulsified at a speed of 8000 rpm and a temperature of 65°C for 150 seconds. Adding additives, an aqueous flame retardant coating having a solid content of 25% was obtained. The aqueous flame retardant coating comprises the following components: by mass, 100 parts of epoxy resin, 16 parts of diethanolamine, 30 parts of polyetheramine, 100 parts of organic solvent, 8 parts of functional filler, and 3 parts of additives, wherein the additives include 1 part of thickener and 2 parts of mildew inhibitor.
[0146] Experiment: Take the water-based flame retardant coating obtained in Examples 1-3 and Comparative Examples 1-5, immerse the wood, immerse at a pressure of 0.8 MPa for 120 minutes, take it out, and cure it at 80°C for 60 minutes, 100°C for 60 minutes, and 120°C for 60 minutes in sequence. A cured layer is formed on the surface of the wood to obtain cured wood. Samples are prepared, and their properties are tested and the test results are recorded:
[0147] Flame retardant performance test: GB 2406.2 is used as the reference standard, and an oxygen index tester is used to test the oxygen index of the cured wood sample. The sample size is 125mm×10mm×4mm;
[0148] Anti-deformation performance test: Using ASTM D2794 as the reference standard, a paint film impact tester is used to test the impact strength of the cured layer sample;
[0149] Water resistance test: GB 30693 was used as the reference standard. A contact angle tester was used to detect the surface water contact angle of the cured layer. The test was started 3s after the water droplet contacted the sample surface. The volume of the water droplet was 4μL.
[0150]
[0151] According to the data in the above table, we can clearly draw the following conclusions:
[0152] The water-based flame retardant coating obtained in Examples 1-3 is compared with the water-based flame retardant coating obtained in Comparative Examples 1-5. The test results show that:
[0153] Compared with the comparative example, the water-based flame retardant coating obtained in Examples 1-3 has a higher limiting oxygen index, impact strength and contact angle data for the cured wood, which fully demonstrates that the present invention achieves improvement in the flame retardancy, deformation resistance and water resistance of wood through the water-based flame retardant coating.
[0154] Compared with Example 1, in Comparative Example 1, boric acid alcohol amine ester is used as a crosslinking agent, specifically prepared from 1,1-dimethoxysilylcyclobutane, octamethylcyclotetrasiloxane, dimethylallylsilylethanol and boric acid; in Comparative Example 2, boric acid alcohol amine ester is prepared from ethanolamine and boric acid, and the crosslinking agent is obtained by reacting the boric acid alcohol amine ester with polyformaldehyde and DOPO-based bisphenol; in Comparative Example 3, boric acid alcohol amine ester is prepared from ethanolamine and boric acid, and the crosslinking agent is obtained by reacting the boric acid alcohol amine ester with polyformaldehyde and bisphenol A; the crosslinking agent in Comparative Example 4 is polyetheramine; compared with Comparative Example 4, the polyvinyl alcohol in Comparative Example 5 is not phosphated. The water-based flame retardant coating obtained in Comparative Examples 1-5 has a decreased limiting oxygen index, impact strength and contact angle data of the cured wood. It can be seen that the preparation process of the water-based flame retardant coating and the components used in the present invention can promote the comprehensive improvement of the flame retardant properties, deformation resistance and water resistance of wood.
[0155] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0156] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A water-based flame retardant coating for wood, characterized in that: The invention comprises the following components: by mass, 100 parts of epoxy resin, 24 to 32 parts of phosphorus-containing polyvinyl alcohol, 30 to 50 parts of crosslinking agent, 100 parts of organic solvent, 8 to 12 parts of functional filler, 3 to 8 parts of auxiliary agent and deionized water; the phosphorus-containing polyvinyl alcohol is obtained by reacting oxidized polyvinyl alcohol with DOPO; The cross-linking agent is prepared by the following process: Mix 1,1-dimethoxysilylcyclobutane, octamethylcyclotetrasiloxane, a catalyst and deionized water, and heat to 80-85°C for reaction for 100-150 minutes under nitrogen atmosphere protection; heat to 90-95°C, add dimethylethoxysilylethylamine, and continue to react for 4-5 hours to obtain amino-terminated siloxane; heat the amino-terminated siloxane to 70-75°C, slowly add dimethylallylsilylethanol, and stir to react for 24 hours to obtain silyl alcohol amine; Mix DOPO and toluene, heat to 85-90°C, and stir for 20-30 minutes; add 4-hydroxy-N-(4-hydroxyphenyl)benzamide, heat to 110-120°C, and reflux for 7-8 hours to obtain DOPO-based bisphenol; The silanolamine and boric acid are mixed in toluene, heated to 110-120°C, and refluxed for 8-10 hours to obtain boric acid alcoholamine ester; the boric acid alcoholamine ester and solvent are mixed, and polyformaldehyde and DOPO-based bisphenol are added, and the temperature is raised to 80-100°C, and the reaction is carried out at a constant temperature for 8-10 hours to obtain a crosslinking agent; The functionalized filler is prepared by the following process: The filler, 3-glycidyloxypropyltrimethoxysilane and alcohol aqueous solution are mixed, the temperature is raised to 60-80° C., and the mixture is stirred for reaction for 3-5 hours to obtain the product.
2. The aqueous flame retardant coating for wood according to claim 1, characterized in that: The solid content of the water-based flame retardant coating is 20% to 30%.
3. The method for preparing a water-based flame-retardant coating for wood according to any one of claims 1 to 2, characterized in that: Including the following processes: Mix epoxy resin and phosphorus-containing polyvinyl alcohol in an organic solvent, heat to 70-80°C under nitrogen atmosphere, add catalyst, heat to 110-120°C, and react for 120-180 minutes; Add a crosslinking agent and a functional filler, and keep the mixture warm at 70 to 80° C. for 60 to 90 minutes; add deionized water, perform shearing, and add an auxiliary agent to obtain a water-based flame retardant coating.
4. The method for preparing a water-based flame-retardant coating for wood according to claim 3, characterized in that: The phosphorus-containing polyvinyl alcohol is prepared by the following process: Mix polyvinyl alcohol and deionized water, heat to 90-95°C to dissolve; add potassium permanganate, stir and react for 5-10 minutes to obtain oxidized polyvinyl alcohol; The oxidized polyvinyl alcohol and DOPO are mixed, and stirred at 70-80° C. for 30-60 minutes; toluene is added, and the temperature is raised to 110-115° C., and refluxed for 100-150 minutes to obtain phosphorus-containing polyvinyl alcohol.
5. The aqueous flame retardant coating for wood according to claim 1, characterized in that: The amino-terminated siloxane comprises the following components: by mole, 1 to 8 parts of 1,1-dimethoxysilylcyclobutane, 2 to 9 parts of octamethylcyclotetrasiloxane, 4 to 25 parts of deionized water, and 2 to 6 parts of dimethylethoxysilylethylamine.
6. The aqueous flame retardant coating for wood according to claim 1, characterized in that: The mass ratio of amino-terminated siloxane to dimethylallylsilylethanol is 100:(5.9-21.5).
7. The aqueous flame retardant coating for wood according to claim 1, characterized in that: The mass ratio of silanolamine and boric acid is (45-158):1; the mass ratio of polyformaldehyde, boric acid amine ester and DOPO-based bisphenol is 1:(25.3-81.4):(3.5-3.9).
Citation Information
Patent Citations
Self-emulsifying antibacterial waterborne epoxy resin and its application in the protection of wood and bamboo materials.
CN110396175B
Coating for ancient building protection
CN111004560A